19+5p+6p-14=14p+15-3p-10

Simple and best practice solution for 19+5p+6p-14=14p+15-3p-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19+5p+6p-14=14p+15-3p-10 equation:


Simplifying
19 + 5p + 6p + -14 = 14p + 15 + -3p + -10

Reorder the terms:
19 + -14 + 5p + 6p = 14p + 15 + -3p + -10

Combine like terms: 19 + -14 = 5
5 + 5p + 6p = 14p + 15 + -3p + -10

Combine like terms: 5p + 6p = 11p
5 + 11p = 14p + 15 + -3p + -10

Reorder the terms:
5 + 11p = 15 + -10 + 14p + -3p

Combine like terms: 15 + -10 = 5
5 + 11p = 5 + 14p + -3p

Combine like terms: 14p + -3p = 11p
5 + 11p = 5 + 11p

Add '-5' to each side of the equation.
5 + -5 + 11p = 5 + -5 + 11p

Combine like terms: 5 + -5 = 0
0 + 11p = 5 + -5 + 11p
11p = 5 + -5 + 11p

Combine like terms: 5 + -5 = 0
11p = 0 + 11p
11p = 11p

Add '-11p' to each side of the equation.
11p + -11p = 11p + -11p

Combine like terms: 11p + -11p = 0
0 = 11p + -11p

Combine like terms: 11p + -11p = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 15x+22y=40 | | 18-8=x/3 | | 7x^(2/3)-13x^(1/3)-2=0 | | 6-18=-4z | | -6(4x-5)+5(5x-3)-6=2-4 | | -3(4x+2)= | | 86-76=39y-44y | | 4w^2+4w+1= | | -4.22-0.807= | | 3x^(1/2)-7x^(1/4)=6 | | -4*10= | | 32x+24y=640 | | 20n+12=16n-16 | | 8x-7=8(x+2) | | 10y-120+3x+45=180 | | 9/5(-10)+32=f | | X+14/13=12/13x | | x+3/12=5/6 | | 9x-(4x-9)=7+4x | | (2x-7)=7 | | 6-8y=5y+19 | | 3t+6t=16-8+28 | | 8(11v)= | | 3^3/2-6=75 | | 40x^2-83x+42=0 | | -25=m-8 | | 3*2-1/5*4+23 | | 2b-5-11b-7= | | 3t+6t=18-8+28 | | 17-1/5(35n+15)=-8n-15 | | ((2*a^-5*b^4*c^3)^-2)/((3*a^3*b^-7*c^3)^2) | | y=3.3x-6.6 |

Equations solver categories